2000
DOI: 10.1063/1.482005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of cryochemical H-tunneling reactions

Abstract: The temperature dependence of tunneling transition of the atomic particle in solids is studied near absolute zero. The different mechanisms of the temperature dependence are considered. They are the medium reorganization, the potential barrier parameters modulation, and the under-barrier friction The nonadiabatic effects are also considered. The rate constant K is described by formula ln K=ln K0+C4T4+C5T5+C6T6+C8T8 at low temperatures. It was conducted through the comparison of theory with the experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…1 In a condensed environment, phonons participate in a tunneling reaction and the environment should have some effect on tunneling reactions. 2,3 However, in several previous experiments it was found that the tunneling rate constant was unaffected by the change of solvent. 1,4 -6 In this work, we have studied the conversion of cis formic acid ͑HCOOH͒ to trans formic acid in solid rare gases ͑Ar, Kr, Xe͒.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…1 In a condensed environment, phonons participate in a tunneling reaction and the environment should have some effect on tunneling reactions. 2,3 However, in several previous experiments it was found that the tunneling rate constant was unaffected by the change of solvent. 1,4 -6 In this work, we have studied the conversion of cis formic acid ͑HCOOH͒ to trans formic acid in solid rare gases ͑Ar, Kr, Xe͒.…”
mentioning
confidence: 97%
“…18͒ and the origin of the effect was considered theoretically. 3,19 The present observations should be valuable in testing theories for the temperature dependence of dissipative tunneling. In addition to the fundamental value the observed phenomenon can be used for solid-phase stabilization of desired species affected by tunneling decay by choosing a suitable environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in temper ature causes the rate constant for tunneling (k) to abrupt ly increase and, after passing through a region with a linear temperature dependence, the parameter lnk obeys the Arrhenius law. 13,14 This type of the temperature de pendence of the rate constants for chemical reactions involving tunneling of an H atom was first explained in More recently, these studies were continued by other authors (see references cited in Refs 13 and 22).…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, isomerization studies performed on hydroquinone and on a halogenated derivative of dihydroxy-benzoquinone isolated in argon matrices [21,22] seem to indicate that the participation of tunneling in isomerization processes involving mainly motion of hydrogen atoms is quite general. Solid-state medium is expected to influence the tunneling rate [23][24][25], which depends also on the temperature due to the participation of the lattice phonons in a dissipative tunneling mechanism [26][27][28].…”
Section: Introductionmentioning
confidence: 99%